Indicators of mobile phone addiction on wellbeing of youth - Munusamy, Kalaivani; Ahmad Ghazali, Akmar Hayati; Mohd Zawawi, Julia Wirza; Mohammad Razi, Siti Aishah (ASR Research India, 2022)
Mobile phones have become ingrained in our daily life. Mobile phone usage increasingly every year and now reaches near 2.4 billion worldwide. In today’s life we cannot look away from our phone screen because we rely on it to communicate and connect with others. Despite the distance separating, mobile phone allows them to interact and integrate regularly. While these advantages are available; mobile phone addiction has become a global problem mainly among youth. However, such social issues seem won’t get much attention, that contributes eventually reduce the understanding of the issue. As a result, this research aims to investigate the factors that indicate mobile phone addiction in relation to psychological characteristics such as extroverts, self-esteem and anxiety. This study was undertaken to investigate the level of extroverts, self-esteem and anxiety towards mobile phone addiction among IPTAs youths in Malaysia. There were employed survey method in this study. The research was carried out on 400 youths from four public universities. These findings conclude that youth’s mobile phone addiction is correlated with psychological characteristic name extroversion, anxiety and self-esteem. This issue must be taken into account before the youths become addicted to problematic usage. To prevent the harmful effects of phone mobile addiction, all the responsible parties such parents and educators need to work together.